2021
DOI: 10.7717/peerj.10943
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the hub gene BUB1B in hepatocellular carcinoma via bioinformatic analysis and in vitro experiments

Abstract: Background Hepatocellular carcinoma (HCC) is one of the most commonly diagnosed cancers and the fourth leading cause of cancer-related deaths in the world. Although the treatment of HCC has made great progress in recent years, the therapeutic effects on HCC are still unsatisfactory due to difficulty in early diagnosis, chemoresistance and high recurrence rate post-surgery. Methods In this study, we identified differentially expressed genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Total RNA was extracted from PDAC cells using RNAiso Plus Reagent (Takara, Japan). qRT-PCR and data analysis were performed as previously described (Fu et al, 2021). Specifically, GAPDH was used as an internal control.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from PDAC cells using RNAiso Plus Reagent (Takara, Japan). qRT-PCR and data analysis were performed as previously described (Fu et al, 2021). Specifically, GAPDH was used as an internal control.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…Cell cycle were measured by flow cytometry. Flow cytometry was performed as previously described (Fu et al, 2021). Briefly, PDAC cells after treatments were fixed in 70% ethanol at −20 C overnight.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…The development of bioinformatics analysis tools combined with in vitro experiments has facilitated the discovery of novel genes and pathways in the progression of human diseases from multiple levels along with the exploration of biomarkers associated with the disease survival, prognosis, diagnosis and treatment. Based on the GEO database and in vitro cell experiments, the current investigation revealed that CTSB could be used as a diagnostic marker for the IR of skeletal muscle in T2DM, and that overexpression of CTSB was able to inhibit palmitate-induced IR in human SkMCs.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, a recent study has demonstrated that CDCA8 promotes HCC growth and stemness through the AKT/β-catenin signaling 53 . BUB1B exerts an oncogenic effect in HCC cell proliferation, migration, and invasion partially by affecting mitochondrial function 54 . CDC20 could enhance cell proliferation and is associated with the development and progression of HCC 55 .…”
Section: Discussionmentioning
confidence: 99%